Comparison of Musculoskeletal Symptoms of Neck and Shoulder among Different Types of Hand Held Device Users - Sabahat Anwar, Rabia Shaheen, Iqra Hameed, Nawal Farooq, Usama Bin Sabir, Tamjeed Ghafar, Efra Akdas, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Prolonged and forceful utilization of hand-held devices has contributed to a global increase in upper extremity and cervical musculoskeletal disorders. These pathologies are directly associated with excessive use of mobile phones and similar devices. Aim: To evaluate the impact of diverse hand-held devices on musculoskeletal (MSK) symptoms in the neck and shoulder and investigate the relation between usage duration and MSK symptoms in the neck and shoulder region. Methods: This study utilized an observational design with a self-structured questionnaire approved by the Department of Physical Therapy at Sargodha Medical College. The sample consisted of 300 young adults aged 21 to 28 years, selected through convenient sampling across different academic years. Data collection involved the distribution of a comprehensive questionnaire, ensuring meticulous responses and privacy. Inclusive criteria included 2nd to final year students, while exclusions maintained homogenity. Results: Among the 300 participants, 76% experienced musculoskeletal discomfort in the neck and shoulder regions, while 24% were asymptomatic. Specifically, 57% reported pain, 16% had numbness, 5% experienced cramping, and 22% felt stiffness. Moreover, 55% of the total population reported some level of pain on Visual Analog Scale, while 45% were pain-free. The study highlights the need for ergonomic design considerations in hand-held devices to minimize the risk of musculoskeletal symptoms in neck and shoulder regions. The findings can guide development of user education programs and workplace interventions to promote proper posture and exercises for individuals using hand-held devices, thereby reducing musculoskeletal discomfort. Conclusion: Excessive utilization of handheld devices is intricately associated with cervico-brachial discomfort, revealing correlations between device typology, duration of usage, postural alignments, and musculoskeletal symptoms. Keywords: Hand-held devices, musculoskeletal symptoms, neck and shoulder discomfort